Teks Anekdot dalam Cerita Lisan Yong Dollah Pewarisan Orang Melayu Sebagai Alternatif Pemilihan Bahan Ajar Bahasa Indonesia - Mukhlis, Muhammad; Asnawi, Asnawi (GERAM: Gerakan Aktif Menulis, 2019)
This research is entitled as "Anecdotal Text in the Oral Story of Yong Dollah Inheritance of Malays as Alternative Choice for Indonesian Language Teaching Materials". It is inspired by the collection of Yong Dollah stories as the inheritance of Malays in Bengkalis Regency which contain of humor elements. In addition, the stories have the same characteristics with anecdotal text, so that it can be applied as teaching material for Indonesia Language subject in the school. This research method was content analysis of descriptive approach. This research was conducted during six months. The technique used to collect data were documentation and interview. The data of this study were the entire generic structure and language features of anecdotal texts contained in a collection of Yong Dollah stories which consisted of 11 stories. The result showed that as following. First, there are five texts contain of complete generic structures and six texts contain of incomplete generic structure which is coda part for data 2, 3, 5, 8, and 1. Second, about language features, there are four data contains of all language features of Anecdote text, but on the other side, there are seven incomplete language features in the texts. Third, the consideration of choosing Yong Dollah as alternative material for Indonesia Language subject refers to eight indicators that are conveyed based on teachers’ perception toward Anecdote text Yong Dolla. 55 % of number of teachers claim that these texts suitable to be implemented as teaching material, but 44% of them claim neutral, and 1% claim disagree on it.